Penyelesaian Konflik Transportasi Angkutan Umum Dengan DAMRI oleh Dinas Perhubungan - Muhammad Firly Rizky Fahreza; Nasrullah Nasrullah (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
Transportation is one of the needs of the community that needs more attention from the government, given that transportation is something that cannot be separated from people's daily lives. Transportation that can deliver tourists to visit Parangtritis beach destinations, one of which is public transportation. Damri's entry into Bantul Regency was due to a program from the central government. This study aims to determine the role of the Bantul Regency Transportation Office in resolving the conflict between public transportation and Damri to support tourism transportation facilities in the Parangtritis area by knowing the supporting and inhibiting factors. The research method uses empirical juridical, with data collection techniques obtained by interviewing the Bantul Regency Transportation Office. The results of this study indicate the role of the Bantul Regency Transportation Office to resolve conflicts between Bantul Regency public transportation and Damri as a mediator. This mediation resulted in a principle where the parties from the Bantul Regency public transportation organization did not question the existence of Damri operating in the Parangtritis area of Bantul Regency with several provisions. But there are supporting and inhibiting factors, the supporting factor is that both parties can be invited and met in a good way to find a solution, the inhibiting factor is the time to bring the two parties together, because of the work or activities of each party. And during this Covid-19 pandemic, crowding activities are also not allowed.